1997
DOI: 10.1148/radiology.202.3.9051012
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic ductal adenocarcinoma: preoperative assessment with helical CT versus dynamic MR imaging.

Abstract: Dynamic MR imaging may be better than helical CT in the preoperative detection and evaluation of local tumor extension and of vascular involvement of pancreatic ductal adenocarcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
88
1
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(106 citation statements)
references
References 0 publications
9
88
1
8
Order By: Relevance
“…1). This result is supported by previous reports in which the excellent ability of MR regarding tumor detection ranging 90 -100%, has been reported (11,24,26,29). This greater conspicuity could be attributed to the intrinsic high soft tissue contrast of MR compared with that of CT.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…1). This result is supported by previous reports in which the excellent ability of MR regarding tumor detection ranging 90 -100%, has been reported (11,24,26,29). This greater conspicuity could be attributed to the intrinsic high soft tissue contrast of MR compared with that of CT.…”
Section: Discussionsupporting
confidence: 91%
“…Peripancreatic soft tissue invasion was diagnosed when the irregularly increased attenuation or signal intensity of the peripancreatic fat layer or spiculated border toward the peripancreatic fat layer on the pancreatic surface was seen (24). Choledochal or duodenal invasion was considered to be present if a suspected hypoattenuated or hypointense lesion directly invaded or reached the surface of the common bile duct and duodenum without evidence of intervening normal pancreatic parenchyma (24). Regional lymph nodes were considered positive when there was a short-axis diameter greater than 10 mm or there was necrosis regardless of its size (32).…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic carcinoma local invasion or extension has been shown as irregular signal intensity in the peripancreatic fat layer, spicular formations with hypointensity on the pancreatic surface, streaky and strand-like signal intensity structures, and mass forming in the peripancreatic fat space on �R imaging [23,[31][32][33] . 18 January 28, 2012|Volume 4|Issue 1| WJR|www.wjgnet.com …”
Section: Mr Imaging Patterns Of Pancreatic Carcinoma Invading Extrapamentioning
confidence: 99%
“…[13][14][15] MRI has also been proved equally efficacious in predicting vascular and nodal involvement. 16,17 CT, however, has limited capacity to characterize the nature of post-radiation soft tissue attenuation. 10 In fact, Katz et al, in their study of 129 patients with borderline resectable pancreatic carcinoma, concluded that radiographic downstaging was a rarity following neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%